Micro Energy Source Using WGMs of Wave in Small Scale Optical Device - R. Siriroj; N. Thammawongsa; P.P. Yupapin (My University, 2013)
Simulation results of forms of waves in a ring resonator system known as a PANDA ring resonator for coated and uncoated materials have been proposed and discussed. The input waves (lights) can be in the forms of soliton, Gaussian pulses, photon or matter wave. The trapped electron motion around the PANDA ring can also be generated, in which the matter wave concept is formed within the PANDA ring waveguide. From the results, we found that the whispering gallery mode (WGM) can be generated due to coupling effects of the two nonlinear side rings, which have shown many interesting results and aspects, especially for energy applications, which can be fabricated and tested on-chip.
Keywords: Matter wave; Quantum optics and atomic interactions